Long-term prognostic value of stress CMR in patients with history of percutaneous coronary intervention. (13th July 2021) - Pezel, T; Hovasse, T; Kinnel, M; Sanguineti, F; Champagne, S; Toupin, S; Unterseeh, T; Garot, P; Garot, J
Abstract: Funding Acknowledgements: Type of funding sources: None. BACKGROUND: Recurrence of cardiovascular (CV) events remains a substantial cause of mortality and morbidity among patients with previous coronary revascularization. PURPOSE: The aim was to assess the prognostic value of stress cardiovascular magnetic resonance (CMR) parameters and CMR-based revascularization in patients with history of percutaneous coronary intervention (PCI). METHODS: Between 2011 and 2014, consecutive patients with history of PCI referred for stress perfusion CMR were followed for the occurrence of major adverse cardiovascular events (MACE), defined by cardiovascular death or nonfatal myocardial infarction. Patients with prior coronary artery bypass graft were excluded. CMR-related coronary revascularization was defined as any revascularization occurring within 90 days after CMR. Univariable and multivariable Cox regressions were performed to determine the prognostic value of each parameter. RESULTS: Of 1, 762 patients who completed the CMR protocol, 1, 624 patients (81.7% male, mean age 67.9 ± 10.4 years) completed the follow-up (median [interquartile range], 6.7 [5.6–7.3] years); 251 experienced a MACE (15.5%). Stress CMR was well tolerated. Using Kaplan-Meier analysis, inducible ischemia and late gadolinium enhancement (LGE) were significantly associated with the occurrence of MACE (hazard ratio, HR: 2.70 [95%CI, 2.11–3.46], p < 0.001; and HR: 1.52 [95%CI, 1.16–1.99], p = 0.002; respectively). In multivariable Cox regression, inducible ischemia and LGE were independent predictors of a higher incidence of MACE (HR: 2.83 [95%CI, 2.20–3.64]; p < 0.001; and HR: 1.42 [95%CI, 1.06–1.91]; p = 0.012; respectively). CMR-related coronary revascularization was associated with a lower incidence of MACE, even after adjustment. CONCLUSIONS: Stress CMR and CMR-related revascularization were independently associated with MACE in patients with history of PCI.